Toulouse/Tolosa, cité des Tolosates et Auch/Elimberris, cité des Ausques : des centres de pouvoir indigènes aux capitales romaines - Philippe Gardes (Gallia)
Recent archaeological research permits us to investigate the circumstances of the birth of two civitas-capitals in south-western Gaul: Toulouse and Auch. These towns succeeded an indigenous centre of power, which was in both cases abandoned after having started on a course of some kind of urban acculturation after the Conquest. This took the form of changes to architecture and to forms of housing. Thus one can observe not only the adoption of Italian building techniques, but also architectural and aesthetic models. The situation changes at the beginning of the Christian era, with the creation of capitals whose programme of urbanism responds to the new administrative and legal requirements of the Augustan reforms.